Tinjauan Hukum Tentang Penertiban Alat Peraga Kampanye - Zahra Alif Cendana; Muhammad Riki Saputra (CV Era Digital Nusantara, 2024)
This journal is motivated by the connection with the problem of violations of the installation of props in campaigns. The orderliness and supervision of campaign tools is one of the stages of a general election campaign. This is fundamental to democracy, namely the existence of a fair and honest General Election system. A fair and honest general electorate can be achieved by complying with laws that manage the election process by protecting prospective candidates, the public, voters, organizers and the general public from fraud, bribery, damaging campaign props or various other things. other events that influence the election results. Therefore, for fair and honest elections there must be legislative regulations regarding elections. So that the condition does not occur. The aim of writing this journal is to find out about the Legal Review which discusses the Control of Campaign Props. This research data was collected from legal research and online journals to fulfill the writing process. The results of this research conclude that the regulations for controlling and installing campaign props are contained in Article 32 in conjunction with Article 34 concerning KPU Regulation Number 23 of 2018, Article 274 of Regulation No. 7 in 2017 then with the latest regulations Article 22 PKPU 15 of 2023 where billboards in the category of Cumulative Campaign Props contain the name of the legislative candidate along with the candidate number and photo and for those passing PKPU No. 3 in 2022 which discusses the implementation and stages of the Schedule sequence in The election will be in 2024. And PKPU regulation Number 3 of 2022, all billboards must be taken down by Satpol PP in accordance with Government Regulation number 16 of 2018 which contains the Pramong Praja police unit.